2020
DOI: 10.21873/invivo.12157
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy and Inhibitory Mechanism of Regorafenib Combined With Radiation in Colorectal Cancer

Abstract: Background: Although both chemotherapy and radiotherapy (RT) can sufficiently maintain tumor suppression of colorectal cancer (CRC), these treatments may trigger the expression of nuclear factor kappa B (NF-ĸB) and compromise patients' survival. Regorafenib suppresses NF-ĸB activity in various tumor types. However, whether regorafenib may act as a suitable radiosensitizer to enhance therapeutic efficacy of RT remains unknown. Materials and Methods: Here, we established a CRC-bearing animal model to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…A large number of studies have enlightened the antitumorigenic properties of colon microbiota-derived SCFAs and their effects in CRC cells [ 2 , 6 , 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Additionally, as described in this review, they can modulate the tumor microenvironment in many distinct ways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies have enlightened the antitumorigenic properties of colon microbiota-derived SCFAs and their effects in CRC cells [ 2 , 6 , 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Additionally, as described in this review, they can modulate the tumor microenvironment in many distinct ways.…”
Section: Discussionmentioning
confidence: 99%
“…This drug is normally used with FOLFIRI to treat metastatic CRC when the cancer continues to progress during or after other treatments. Another available biological drug is regorafenib (Stivarga) that acts as a multi-kinase inhibitor, namely through the inactivation of angiogenic and oncogenic kinases, such as VEGF 1–3, fibroblast growth factor receptor 1, EGFR, RAF, and tyrosine-protein kinase [ 18 , 20 ]. It is designed to treat patients with metastatic colon cancer whose cancer has continued to advance after approved standard therapies [ 18 , 20 ].…”
Section: Colorectal Cancer Therapeutic Challengesmentioning
confidence: 99%
“…Besides synergizing with ICIs, regorafenib may also enhance the radiosensitivity of colorectal tumors by blocking radiation-induced activation of receptor tyrosine kinases, inhibiting VEGF-mediated angiogenesis, and suppressing DNA damage repair ( 17 , 18 ). However, only a few studies have demonstrated these effects of regorafenib using tumor cell lines and mouse models, and no clinical trials investigating regorafenib in combination with radiotherapy have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The mice were anesthetized with 1%–3% isoflurane during computerized tomography scanning on Days 0 and 10 of treatment. The operation parameters of tube energy were 55 kVp × 145 μA, and the scanning resolution was 145 × 145 × 145 μm with 360 projections of direction 28 …”
Section: Methodsmentioning
confidence: 99%
“…The operation parameters of tube energy were 55 kVp  145 μA, and the scanning resolution was 145  145  145 μm with 360 projections of direction. 28…”
Section: Whole-body Computed Tomography Scanningmentioning
confidence: 99%